2004
DOI: 10.1039/b410805a
|View full text |Cite
|
Sign up to set email alerts
|

Salt-induced protein resistance of polyelectrolyte brushes studied using fluorescence correlation spectroscopy and neutron reflectometry

Abstract: We used two-photon excitation fluorescence correlation spectroscopy (FCS) and neutron reflectometry to study in situ the effect of salt concentration on the degree of protein binding to polyelectrolyte brushes. The binding of bovine serum albumin (BSA) to poly(acrylic acid) (PAA) brushes was characterized at neutral pH values where both the protein and the brushes carry a negative charge. Spherical PAA brush particles were used in the FCS experiments, whereas a planar PAA brush served as protein substrate in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
76
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(79 citation statements)
references
References 44 publications
2
76
0
Order By: Relevance
“…[55] layer becomes more and more protein resistant. [55,61] In this regime, the steric repulsion between the dissolved proteins and the brush layer of the SPB finally becomes operative and only marginal adsorption results. [55] (2) Previous studies by FT-IR have shown that the secondary structure of the adsorbed BSA, b-lactoglobulin and of ribonuclease A is nearly undisturbed.…”
Section: Immobilization Of Proteins and Enzymes On Spherical Polyelecmentioning
confidence: 98%
“…[55] layer becomes more and more protein resistant. [55,61] In this regime, the steric repulsion between the dissolved proteins and the brush layer of the SPB finally becomes operative and only marginal adsorption results. [55] (2) Previous studies by FT-IR have shown that the secondary structure of the adsorbed BSA, b-lactoglobulin and of ribonuclease A is nearly undisturbed.…”
Section: Immobilization Of Proteins and Enzymes On Spherical Polyelecmentioning
confidence: 98%
“…Moreover, the protein insulin does not transform into amyloid fibers when attached to PAA brushes even at conditions at which fibrillization is normally observed [75,78]. In contrast to low salt concentrations PAA brushes become highly protein resistant at high salt concentrations as these conditions suppress the process termed 'counterion evaporation' which is the major driving force for protein adsorption to polyelectrolytes [79,80].…”
Section: Influence Of Surface Properties On Protein Adsorptionmentioning
confidence: 99%
“…This technique has been applied to brushes prepared using both grafting-to 8,10,[35][36][37] and grafting-from methods. Recently, a number of studies have been performed of grafted-from brushes prepared using methacrylate ATRP, focusing on a variety of weak pH-responsive brushes 11,21,34,38,39 , as well as strong polyelectrolyte brushes 21,40,41 and polyampholytes 22 .…”
Section: Introductionmentioning
confidence: 99%
“…For example, polyelectrolyte brush-like structures are important for the stabilization of colloidal casein particles in milk 1 and have been implicated in lubrication at the ocular surface [2][3][4][5] , while synthetic polyelectrolyte brushes have found applications including the stabilization of colloidal suspensions of synthetic nanoparticles 6 , and production of responsive, protein resistant and biofunctional surfaces [7][8][9] . The properties of polyelectrolyte brushes, including their structure [10][11][12] , mechanical and lubrication properties [13][14][15][16] , and their responses to changing pH and electrolyte conditions 10,11,[16][17][18][19][20][21][22][23] have thus been widely investigated (for reviews see e.g.…”
Section: Introductionmentioning
confidence: 99%